Pengaruh Leverage, Ukuran Perusahaan, Pertumbuhan Laba, dan Profitabilitas terhadap Kualitas Laba: Studi pada Perusahaan Basic Materials yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Gita Desyana; David Gowira; Miranda Jennifer (Jurnal Eksplorasi Akuntansi, 2023)
This research aims to study how leverage, firm size, profit growth, and profitability affect earnings quality. The study uses quantitative approach with associative method. Basic Materials companies that listed on Indonesia Stock Exchange in 2017-2021 with total of 97 companies are the population used in the study. Researchers use purposive sampling in selecting samples resulting in 67 companies meeting the criteria determined. Data used is secondary data obtained using documentation observation method from www.idx.co.id. With total of 335 data collected, researchers use multiple linear regression with the SPSS 25 programs. Results show that firm size has significant positive effect on earnings quality. Meaning that larger company has higher earnings quality. In contrast, earnings quality is not significantly affected by leverage, profit growth and profitability of firm. Further researches are hoped to expand the observation period, use other variables, and study other sector of company to show better result.